Ligand effects on the structure and vibrational properties of the thiolated Au18 cluster - Tlahuice Flores, Alfredo (Elsevier, 2016)
Most of the studies devoted to thiolated gold clusters suppose that their core and Au-S framework do not suffer from distortion independently of the protecting ligands (-SR) and it is assumed as correct to simplify the ligand as SCH3. In this work is delivered a systematic study of the structure and vibrational properties (IR and Raman) of the Au18(SR)14 cluster. The pursued goal is to understand the dependency of the displayed vibrational properties of the thiolated Au18 cluster with the ligands type. A set of six ligands was considered during calculations of the vibrational properties based on density functional theory (DFT) and in its dispersioncorrected approach (DFT-D)